Editorial to the Proceedings of the TensiNet - COST Action TU1303 Symposium 2016 - Chilton, John; Gosling, Peter; Mollaert, Marijke; Stimpfle, Bernd (Elsevier, 2016)
The TensiNet Association, in collaboration with the COST Action TU1303 “Novel structural skins: Improving sustainability and efficiency through new structural textile materials and designs” and the Newcastle University organized the TensiNet - COST Action TU1303 Symposium 2016 held in Newcastle upon Tyne, UK, from Wednesday 26th to Friday 28th October 2016.